Enhancing image-emoji graphical password multi-factor authentication by utilizing single touch and multi-touch gesture - Roslan, Nuur Alifah; Mohd Norowi, Noris; Zabidi, Nursyabila; Mahmod, Ramlan; Asfarian, Auzi (Semarak Ilmu, 2024)
Smartphones have evolved into a basic human requirement. PINs, passwords, swipes and other methods are used to authenticate users on mobile devices. However, existing authentication systems are vulnerable to modern security vulnerabilities. As the number of touch devices increases, gesture-based authentication becomes increasingly crucial. The distinctness of a gesture in a touch base mobile device is investigated in this research. Analysis reveals that a specific user has distinct finger gestures. An experimental study demonstrates that an individual's index finger and thumbs improve finger accuracy in a gesture-based authentication. The purpose of this article is to investigate the influence of single and multi-touch on the production of graphical passwords, specifically using images and emoji and based on a two-factor authentication mechanism. Our finding proves the efficiency increasing up, where it took an average of 37 seconds to register their credentials when using the multi-touch gesture approach compare 47.93 seconds on average for single-touch approach. As for the effectiveness, which referring the trial attempts determined that multi-touch gestures are more successful than single touch gestures, with a 78% success.